187k views
1 vote
6x - 2y = 26

2x + 3y = 5

Solve for X and Y

User UtopiaLtd
by
4.8k points

1 Answer

3 votes

Answer:

y is equal to -1

x is equal to 4

Explanation:

The first thing you would do is multiply the bottom equation by a negative 3. You will get - 6x - 9y = -15. Keep the top equation the same. Both of the 6x's cancel. You then get -11y = 11 so y is equal to negative 1.

Since you have Y, you can now plug that in to any equation to find the value of x. -6x - 2(-1) = 26. You're left with 4. Plug both of the values into each equation to double check.

User Shahrukh Mohammad
by
5.5k points